Sosialisasi Pentingnya Moderasi Beragama sejak Dini melalui Video 'Berbeda Itu Indah' dalam Upaya Membangun Toleransi Santri Taman Pendidikan Al-Qur'an (TPQ) Jawahirul Qur'an - Mohamad Mujahid Islamudin; Yeni Mukhlisoh; Wulan Nur Hardiana; Rohmatul Aini; Radinna Maulida Mahezwari (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Indonesia’s religious and cultural diversity requires early religious moderation education to prevent intolerance and promote harmonious social interaction. However, most Quranic Learning Centers (TPQ) do not yet implement a structured and developmentally appropriate model for teaching moderation values to children. This program aimed to enhance students’ understanding of tolerance through a socialization activity using the animated video “Berbeda Itu Indah” (Differences Are Beautiful) combined with group discussions, role-play, and LOTS-based evaluation. The activity involved 200 students aged 6-12 and was conducted over 90 minutes, including video screening, guided dialogue, interactive simulations, and a five-item oral quiz for volunteers. Results indicate a participation rate above 85% and improved comprehension, reflected in students’ ability to express tolerant actions such as respecting peers of different religions and resolving disagreements peacefully. The use of audiovisual media effectively supported the concretization of abstract concepts, while a simple reward system increased learning motivation. Despite limitations in duration and supporting media, the program successfully fostered foundational moderation values and provides a replicable instructional model for other TPQ institutions. These findings reinforce the effectiveness of audiovisual-interactive approaches in cultivating early tolerance and religious moderation among children.